Factors affecting response and resistance to venetoclax in acute myeloid leukemia - Diamantidis, Michael D. (Frontiers in Oncology, 2025)
The use of the BCL2 inhibitor venetoclax in combination with hypomethylating agents (HMA) is a revolution for the treatment of frail and elderly acute myeloid leukemia (AML) patients. This effective treatment strategy is increasingly more and more applicable for other subsets of AML patients and is currently being tested in numerous clinical trials in combination with other drugs in all treatment lines. In particular, venetoclax combinations can also serve as a definitive therapy or as an effective bridge to allogeneic hematopoietic stem cell transplantation (HSCT). However, the factors affecting response to venetoclax in the abovementioned AML patients are not completely clear and understood until today. The aim of this review is to describe the molecular and clinical patterns of response and durable remission of venetoclax-based combinations in AML patients. Hence, mutations in IDH1, IDH2, ASXL1, NPM1, DDX41, chromatin-cohesin complex and splicing-factor genes predict superior response to venetoclax, while inferior response to the drug has been observed for FLT3-ITD, KRAS, NRAS and TP53 gene mutations. Intriguingly, the achievement of measurable residual disease (MRD) negativity in the first four cycles of venetoclax administration characterizes a subgroup of NPM1-mutated AML patients with a more favorable outcome. Even though focus will be given on factors influencing response to the drug in this review, the main mechanisms of resistance to venetoclax in AML patients will also be discussed.